A comprehensive and practical guide to clinical trials - Shamley, Delva; Wright, Brenda; ScienceDirect eBooks (London, United Kingdom : Academic Press, 2017)
A Comprehensive and practical guide to clinical trials provides an overview of the entire process of clinical research in one thorough and easy-to-read handbook that offers those involved in clinical research a clear understanding of how the components of a study are related. It focuses on the practical aspects of the preparation and execution of a clinical trial and offers tools and resources to help the entire team understand how their responsibilities tie together with the tasks and duties of other members. This allows for better planning and prioritization, and can lead to more effective and successful clinical trials. With practical examples, checklists and forms, this book is a useful guide for planning and conducting clinical trials from beginning to end. Describes the entire clinical trial management process from start to finish in a step-by-step guide. Provides best practice elements, including case studies, practical examples, activities, and checklists.
Appendix 7.5 Study BudgetAppendix 7.6 Staff Work Schedule; Appendix 7.7 Stock List; Appendix 7.8 Emergency Trolley Checklist; Appendix 7.9 Status Report; 8 Recruitment and Retention; Recruitment; Motivations for Participating in a Clinical Trial; Why Participants Will not Join; Recruitment Challenges; Recruitment Options; Achieving Recruitment Targets; Retention; Signs of Potential Nonadherence; Reasons for Resistance; Useful Tips for Participant Retention; Further Reading; 9 Training; Internal Training; External Training; Further Reading; 10 Data Management; Establish Compliance Requirements
Includes bibliographical references and index.
Vendor-supplied metadata.
Elsevier
Keywords: Clinical trials -- Handbooks, manuals, etc; HEALTH & FITNESS / Holism; HEALTH & FITNESS / Reference; MEDICAL / Alternative Medicine; MEDICAL / Atlases; MEDICAL / Essays; MEDICAL / Family & General Practice; MEDICAL / Holistic Medicine; MEDICAL / Osteopathy; Clinical trials; Electronic books